Synthesis and Reactions of α-Hydroxyphosphonates - Zita Rádai; György Keglevich (Molecules, 2018)
This review summarizes the main synthetic routes towards α-hydroxyphosphonates that are known as enzyme inhibitors, herbicides and antioxidants, moreover, a number of representatives express antibacterial or antifungal effect. Special attention is devoted to green chemical aspects. α-Hydroxyphosphonates are also versatile intermediates for other valuable derivatives. O-Alkylation and O-acylation are typical reactions to afford α-alkoxy-, or α-acyloxyphosphonates, respectively. The oxidation of hydroxyphosphonates leads to ketophosphonates. The hydroxy function at the α carbon atom of hydroxyphosphonates may be replaced by a halogen atom. α-Aminophosphonates formed in the nucleophilic substitution reaction of α-hydroxyphosphonates with primary or secondary amines are also potentially bioactive compounds. Another typical reaction is the base-catalyzed rearrangement of α-hydroxy-phosphonates to phosphates. Hydrolysis of the ester function of hydroxyphosphonates leads to the corresponding phosphonic acids.